Distribution and fertility of the spider Latrodectus tredecimguttatus (Rossi, 1790) (Aranei: Theridiidae) in the Odessa region (Ukraine) - Deli, O.; Pidhorna, S.; Chernychko, K. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Population dynamics of the black widow spider depends primarily on climatic conditions (short warm winter, wet spring, and hot summer cause an increase in individuals numbers) and secondary – depends on forage base and the number of enemies (parasitoid wasps). Therefore, constant monitoring of black widow spiders in the Odessa region is really important. This article provides data on distribution of the spider Latrodectus tredecimguttatus (Rossi, 1790) obtained in 2014‒2018 in the Odessa Region (Ukraine). Preliminary surveys were conducted in all districts of the region, and black widow spiders were registered in ten out of 26 districts (Artsyzsky, Bilhorod-Dnistrovsky, Bilyaevsky, Bolgradsky, Izmailsky, Kiliysky, Limansky, Ovidiopolsky, Reniysky, Tatarbunarsky). Mainly, the black widow spiders occurred in the southern districts of the region. Black widow spiders were found to be more common in ruderal habitats (54% of the total individuals collected) and rarer in agrocenoses (12%), saline marshes and steppe areas (17% each). The number of eggs and number of cocoons made by one female were counted. The number of eggs in one cocoon ranged from 276 to 458, and the number of cocoons woven by one female – from one to seven. In the study area, intensive cocoon making and egg laying by the black widow spiders was observed in early July; then the intensity decreased gradually in August. The largest number of the black widows’ cocoons was found in three southern districts of the Odessa Region (Bolgradsky, Izmailsky, and Reniysky). The largest number of eggs in one cocoon was registered in the Reniysky district while the smallest number of eggs was recorded in the Bilhorod-Dnistrovsky (613) and Bilyaivsky (903) districts. The largest average number of eggs laid by one female was fixed in Reniysky (2710) and Bolgradsky (2571) districts. Moreover, in these two districts located in the south of the Odessa Region, the largest number of the black widows’ nests was found. The smallest number of nests was recorded from three districts: Artsyzsky, Bilyayevsky and Limansky.